Bimbingan Kelompok Untuk Meningkatkan Motivasi Berprestasi Pada Anak Panti Sosial - Ramadhoni, Sri Rahmah; Mungin Eddy, Wibowo; Cahyani, Anugrah Intan; Amriana, Amriana (Jurnal Bimbingan dan Konseling Islam, 2023)
The purpose of this research is to determine the effectiveness of group guidance to increase achievement motivation of Children's Orphanage "Aisyiyah" Semarang City. The research method is an experiment using the design of one group pre-test and post-test by involving 26 Children's Orphanage "Aisyiyah" Semarang City who had low achievement motivation. The data collection used was achievement motivation scale. The data were analyzed using dependent t test analysis using paired sample t test. The results showed that the achievement motivation of orphanage children before group guidance was carried out the average (mean) of children's achievement motivation was 19.54. After group guidance, the average (mean) of children's achievement motivation increased by 31.38. The test results to determine whether group guidance is effective in increasing children's achievement motivation that there is a difference in the average value of children's achievement motivation levels before and after group guidance is -11.846. The magnitude of the calculated t value is -21.946 with a probability of 0.000. This means that there is a significant difference in the level of children's achievement motivation before and after group guidance. These findings confirm that group guidance can be applied to increase student achievement motivation.